Temat muzyki we współczesnej literaturze litewskiej - Peluritytė-Tikuišienė, Audinga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Music is not a very topical theme in contemporary Lithuanian literature. The Lithuanian literature saved its meditative and visual nature during the most difficult epoch of historical and social cataclysms, and only some romanticists and symbolists talked about an exceptional music effect on human organism (prosaist Šatrijos Ragana, poet Vincas Mykolaitis-Putinas). Only few auhtors invoke the tune and symbolism of music in contemporary Lithuanian literature. A. A. Jonynas, one of the most popular poets, created verses in the rythm of jazz, swing, hard rock, metal, rock‘n‘roll during the Soviet period. The idea of music lived the freedom of form, the idea of freedom in general in that creation. Postmodernist G. Grajauskas choosed the tune of music in his book Bone pipe (1999) in order to discuss difficult existential questions. Playing, whistling, singing means the rythm of breathing and existence in that creation. The sense of musical harmony is more likely to be associated with the experience of silence in contemporary Lithuanian literature (G. Cieškaitė, D. Kajokas, N. Miliauskaitė).